ENT 530 : Case Study: Mouthgasm Crunchy Sdn Bhd / Nurul Jannah Mohd Noor ... [et al.] - Mohd Noor, Nurul Jannah; Rosli, Nur Fatihah; Kamarudin, Nursaffaren; Mohd Asri, Nurul Anis Amila; Mohd Kamari, Muhammad Amiruddin (2021)
Case study was conducted in order to have a better understanding of the concept of reallife business, as well as to identify and solve the fundamental difficulty that Small and Medium Enterprises (SME's) confront especially during this Covid-19 pandemic. In response, we have chosen Mouthgasm Crunchy Sdn Bhd as a part of our case study. The findings of the case study are based on the online interview that have been carried on with Mr. Shahrul Shafiq as the business owner to get the information about his business. A brief description of his company, Mouthgasm Crunchy Sdn Bhd is a Malaysian SME that was established in December 2019. It is operated as online based selling and owned by Mr. Shahrul Shafiq, who is a university graduate in architectural and enjoys business. This business offers customers a food and snack-based products that is a combination of Choco crunch and cookies flake in mocha chocolate flavour with toppings of coffee powder. This product has now become well-known, particularly among chocolate and caffeine enthusiasts. This research will comprise the general information of the company such as the background, organizational structure, products and services offered by Mouthgasm Crunchy Sdn Bhd as well as the business, marketing and operational strategy that they use in order to run a successful company. The further discussion will be the analyzation of SWOT analysis which includes the company's strengths, weaknesses, opportunities, and threats. This provides us on the information on how they managed the organization and sustain running business using well-strategic plan and the opportunities that they had. The threat and weaknesses will be identified for the Mouthgasm Crunchy Sdn Bhd improving their business. Small and Medium Enterprise (SMEs) are the most typical type of business that faces financial difficulties during economic downturns and pandemics. As a result, many small- and medium-sized business owners including Mouthgasm Crunchy Sdn Bhd are striving to stay afloat in their respective industries. The major problem that can be found in this research is they lacking in machinery system as well as challenge in exporting product. A limited resources can affect the production. Lastly, this research as well conclude the major problem that company faced and the recommendation for the SMEs to act to the problem that they faced. Therefore, lead us to the reality of the business world, especially in SME’s.